Orchids of the Southern Cone (1830–2000) – Part I Claude Gay’s physical and political history of Chile - Ossenbach, Carlos (Universidad de Costa Rica, 2022)
The life and works of French botanist Claude (Claudio) Gay (1800–1873) are presented, with special consideration to Orchidaceae. This work aims to bring to light the life of a brilliant scientist who dedicated his professional life to the study of Chile’s natural history and his seldom-mentioned monumental work that contains the first complete orchid flora of Chile. The most important modern and contemporary bibliographical sources have been consulted, as well as Gay’s original publications. Claude (Claudio) arrived in Chile in 1828 and lived in the country until 1842, engaged by the Chilean government to conduct a scientific survey of the country. He traveled across the country collecting objects of natural history which became the foundation stone of the Cabinet of Natural History, the precursor of Chile’s National Museum of Natural History. Gay returned to France in 1842 and, commissioned by the Chilean Minister of the Interior, published his Historia física y política de Chile, a monumental work in 30 volumes that were published between 1844 and 1871. Eight volumes, published in Paris between 1845 and 1852, containing 3767 species of plants, were dedicated to botany. Following the incomplete works of Juan Ignacio Molina’s Saggio sulla Storia Naturale del Chili (1782) and Ruiz and Pavon’s Flora Peruvianae et Chilensis (1789–1803) it was the first attempt to produce a complete flora of Chile. A total of 49 species of Orchidaceae were described and partly illustrated, a remarkable achievement if we consider that by the turn of the 21st century, a total of orchids was only 52 had been reported for Chile. Claudio Gay is considered the first recorder of the country’s history and the founder of modern natural science in republican Chile.